Comparison of Acoustic Emission Data Acquired During Tensile Deformation of Maraging Steel M250 Welded Specimens - WURITI, Gowri Shankar; CHATTOPADHYAYA, Somnath; KROLCZYK, Grzegorz (Archives of Acoustics, 2020)
Safety and reliability are primary concerns in launch vehicle performance due to the involved costs and risk. Pressure vessels are one of the significant subsystems of launch vehicles. In order to have minimal weight, high strength material viz. maraging steel M250 grade is used in realizing the pressure vessel casing hardware. Despite the best efforts in design methodology, quality evaluation in production and effective structural integrity assessment is still a farfetched goal. The evolution of such a system requires, first, identification of an appropriate technique and next its adoption to meet the challenges posed by advanced materials like maraging steels. In fact, a quick survey of the available Non-Destructive Evaluation (NDE) techniques suggests Acoustic Emission (AE) as an effective structural integrity assessment tool capable of identifying any impending failure or degradation at an earlier stage. Experience shows that the longitudinal welds in the pressure vessels are quite vulnerable to failure due to the fact that they experience the maximum stress (i.e. hoop stress). Loading welded tensile samples are quite synonymous to the hoop stress experienced by longitudinal welds. An attempt is made to compare the Acoustic Emission data acquired during tensile deformation of maraging steel welded specimens. A total of 16 welded specimen’s with known defects were studied for their tensile behaviour is in connection with Acoustic Emission data. The lowest failure load was 70.5 kN and the highest being 84.8 kN. AE activity graphs viz. cumulative AE activity, hit rate, energy rate, count rate, AE amplitude history, AE count history, AE energy history, amplitude-count correlation and hit amplitude distribution have been investigated and salient features with respect to the data have been critically studied and relevant correlations are arrived at.